2016
DOI: 10.1016/j.krcp.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of uremic pruritus between patients undergoing hemodialysis and peritoneal dialysis

Abstract: BackgroundUremic pruritus is a common, but unpleasant, complication of end-stage renal disease. The uremic burden may differ between hemodialysis (HD) and peritoneal dialysis (PD) patients. This difference may also change the clinical characteristics of uremic pruritus between the 2 modalities. In this study, we investigated the uremic pruritus between patients on HD and PD.MethodsA total of 425 HD and 223 PD patients from the Clinical Research Center registry in Korea were included. Patients were assessed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
54
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 18 publications
6
54
1
9
Order By: Relevance
“…With regards to UP characteristics, our results found that severe pruritus was observed in the studied population, as represented by a median VAS of 7 (5-8), according to the adopted classification in previous studies [9,17,20]. It is important to note that some studies have found an increased mortality risk in patients undergoing dialysis associated with severe pruritus, e.g., when the pruritus VAS score was greater than 7 [17,21].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…With regards to UP characteristics, our results found that severe pruritus was observed in the studied population, as represented by a median VAS of 7 (5-8), according to the adopted classification in previous studies [9,17,20]. It is important to note that some studies have found an increased mortality risk in patients undergoing dialysis associated with severe pruritus, e.g., when the pruritus VAS score was greater than 7 [17,21].…”
Section: Discussionsupporting
confidence: 53%
“…When comparing UP prevalence in patients undergoing HD or peritoneal dialysis, Min et al [9] found a greater prevalence among those who underwent peritoneal dialysis compared to HD and ascribed this finding to the fact that these patients did not use high-flux dialyzers; thus, average-sized inflammatory molecules were not removed. Dialysis adequacy has a fundamental role in metabolic control and the clearance of possible pruritogenic substances, which may result in the attenuation of UP-associated factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In a cross-sectional study of 223 PD and 425 HD patients from Korea, the prevalence of at least mild pruritus was 62.5% in HD patients and 48.3% in PD patients. 22 Several studies have compared CKD-aP prevalence rates in HD and PD patients with mixed results. Two studies found no difference in pruritus rates, 23,24 whereas one study found higher rates of pruritus in PD patients, 22 and one found higher rates of pruritus in HD patients.…”
mentioning
confidence: 99%
“…22 Several studies have compared CKD-aP prevalence rates in HD and PD patients with mixed results. Two studies found no difference in pruritus rates, 23,24 whereas one study found higher rates of pruritus in PD patients, 22 and one found higher rates of pruritus in HD patients. 25 These mixed results are likely due to the varied study populations and the different instruments used to measure CKD-aP in these studies.…”
mentioning
confidence: 99%